Implementation of INLISLite in the Library of SMA Negeri 1 Padang Sago - Lisa Davici; Ade Pratama; Anggri Yulio Pernanda (JURTEII: Jurnal Teknologi Informasi, 2023)
This study aims to implement a computerized library information system using INLISLite, and find out the results of the validity of its use in libraries. This research uses the method of reuse based software engineering to be used in the implementation stage, using parallel conversion techniques. The results showed that the INLISLite-based library information system that has been implemented can bring many benefits to libraries in managing collections faster and saving time, especially in inputting data such as member registration, book collection, book borrowing, book returns, and reporting. The validity of this system has been tested by providing questionnaires to validators and system users, which showed that the system and beta tested assessment of all validation results reached an average of 90.14% with the category of very valid.